Electromagnetic wave propagation in a fast pulse line ion accelerator. Issue 12 (4th November 2019) - Behbahani, Reza A.; Diot, Quentin; Kavanagh, Brian; Serkova, Natalie J.; Miften, Moyed; Westerly, David C.
Abstract : Purpose: The pulse line ion accelerator (PLIA) is a low‐cost accelerator concept originally designed to accelerate heavy ions. Our group has been investigating the use of PLIA to accelerate light ions and believe a multi‐stage PLIA could be useful for short half‐life PET isotope production. The goal of this work was to develop a single prototype fast PLIA structure and demonstrate electromagnetic wave propagation using a high‐voltage pulser. Materials and methods: A 1.6 m fast PLIA structure (wave speed > 10 7 m/s) was constructed along with a high‐voltage, sinusoidal pulse generator. The latter uses capacitive voltage doubling and spark gap switching. A step‐up transformer couples voltage from the pulser to the PLIA coil. Voltage measurements on the coil were made in air using a high‐voltage resistive probe, while capacitive probes placed along the length of the PLIA were used to measure wave propagation with the PLIA structure filled with transformer oil. Results: Voltage measurements acquired on the primary and secondary coils of the transformer coupler in air demonstrated a peak‐to‐peak voltage step‐up of 4.2 relative to the pulser DC charging voltage. The maximum voltage time‐rate‐of‐change on the PLIA coil was 0.76 × 10 13 V/s. Capacitive probe measurements indicated voltage oscillations on the PLIA coil with half‐period equal to 43 ± 0.9 ns and wave speed (with oil) of 1.2 × 10 7 m/s. Average and peak accelerating gradients were conservatively estimated to be 0.44 and 0.60 MV/m, respectively, with a charging voltage of 55 kV. Wave propagation was demonstrated at these gradients without flashover at a vacuum pressure of 9 × 10 −6 Torr. Submerging the pulser in oil would allow for charging voltages up to 150 kV and produce accelerating gradients >1.2 MV/m. Conclusions: Use of a multi‐stage, fast PLIA for light ion acceleration could provide a low‐cost complement to cyclotrons for the production of short half‐life isotopes used for PET imaging, including carbon‐11, nitrogen‐13, oxygen‐15, and fluorine‐18.